Legal aspects of safety in medical procedures - Niyazbekova, Lazzat (Medicine, law & society, 2025)
This paper examines the legal regulation of medical procedure safety and proposes avenues for legislative enhancement informed by international norms. A comparative legal analysis was performed utilising the cases of Bulgaria, Italy, and Kazakhstan. The study utilised a systematic methodology to evaluate legal efficacy and predictive techniques to delineate potential advancements. The findings reveal that all three countries acknowledge the right to healthcare at the constitutional level, but implementation strategies vary. Bulgaria and Italy utilise insurance-based healthcare systems that incorporate private sector involvement. Bulgaria faces challenges in harmonising its law enforcement with European norms, whilst Italy's decentralised Servizio Sanitario Nazionale results in regional disparities. Kazakhstan upholds a state-centric regulatory framework but lacks comprehensive legal safeguards for patients and medical practitioners, especially concerning liability insurance. No country possesses a comprehensive legal framework for digital medicine. Key proposals include improving insurance protections, harmonising national laws with international norms, and regulating emerging medical technologies.
Keywords: civil liability; healthcare; licensing; regulatory framework; state regulation